New Entropy Pythagorean Fuzzy Set And Its Application In Multicriteria Decision Making - Munandar, Arif (Jurnal Matematika UNAND, 2025)
In this study, a new entropy measure for Pythagorean fuzzy sets is proposed. The validity of the entropy is rigorously verified through the satisfaction of keyaxiomatic properties such as minimality, maximality, symmetry, and resolution. Oncevalidated, the newly developed entropy is applied to a multi-criteria decision-making(MCDM) problem using the TOPSIS method. The integration of this entropy with TOPSIS provides a robust and systematic approach to determining optimal alternatives indecision-making scenarios involving uncertainty and imprecision. The proposed methodenhances the ability to model and analyze complex problems, thereby contributing a noveland effective tool to the field of fuzzy decision-making